2011
DOI: 10.1016/j.jvs.2011.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of a preclinical endovascular skills course on medical student career choices

Abstract: Basic endovascular skills can be efficiently introduced through a simulation-based curriculum and lead to improved novice performance. Early exposure of preclinical medical students provides an effective teaching and recruitment tool for procedural-based fields, particularly surgical subspecialties. Mentored exposure to endovascular procedures on the simulator positively impacts long-term medical student attitudes toward vascular surgery and ultimate career choices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 20 publications
(31 reference statements)
1
26
0
1
Order By: Relevance
“…3,31,32,36,49,56,61,74,91,96,97,[106][107][108][109][110][111][112][113][114][115][116][117][118][119][120] Clinical experience is known to have a significant impact on career decisions, but the mentorship during exciting clinical opportunities may lead to an especially transformative ex perience during surgical clerkship. We encourage that mentor relationships be established with medical students whenever possible and that same-gender mentors are more favourable if available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,31,32,36,49,56,61,74,91,96,97,[106][107][108][109][110][111][112][113][114][115][116][117][118][119][120] Clinical experience is known to have a significant impact on career decisions, but the mentorship during exciting clinical opportunities may lead to an especially transformative ex perience during surgical clerkship. We encourage that mentor relationships be established with medical students whenever possible and that same-gender mentors are more favourable if available.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of surgical simulation training on developing medical student interest in surgery was assessed in 4 studies identified by our search strategy. [72][73][74][75] Surgical simulation training improved student experience of surgical clerkship in all of these studies and improved interest in surgery in 2 studies. 73,74 Galiñanes and colleagues 72 found that orientation to basic laparoscopy can benefit a student's clerkship experience, but does not improve student interest in surgery.…”
Section: Clinical Exposurementioning
confidence: 99%
“…Based on the parameters assessed, 12 studies were classified as “high risk” for internal validity [[6], [7], [8], [9], [10],[12], [13], [14], [15], [16], [17], [18]] and 5 as “low risk” [[19], [20], [21], [22], [23]]. Sixteen studies used a representative population of undergraduate students and were therefore considered as low risk for external validity.…”
Section: Resultsmentioning
confidence: 99%
“…Interviews with Internal Medicine house staff revealed that they were often steered toward Pulmonary and Critical Care Medicine by their ICU experiences, specifically by the high-stakes medicine, the ability to see physiology in action, exposure to strong role models, and the ability to care for a wide range of issues (45). Early medical student exposure to other fields including surgery (46), vascular surgery (47), and primary care (48,49) has been shown to positively influence their career choice.…”
Section: Opportunitiesmentioning
confidence: 99%